The beginnings of the Phoenician presence in Cadiz - Padilla Monge, Aurelio (Gerión. Revista de Historia Antigua, 2014)
I defend in this paper the hypothesis that the structures set up by the Phoenicians in the North of the present peninsula of Cadiz, from the late ninth century or early eighth century B.C. onward, were mainly devoted to the religious activities of the settlers established in the colony of Doña Blanca and that fish processing labours were also carried out in the ancient island of Cadiz. Likewise, I argue that these buildings became, over the course of the sixth century B.C., both an important population entity from a demographic point of view, on account of the arrival of people from the Phoenician colonies sited in the Low Guadalquivir and the area of Huelva, a territory in which the Canaanite colonial world collapsed, and an important centre from a political and economic point of view, to a great extent due to the disappearance of the quoted colonial horizon.
Keywords: Phoenician colonization; Pre-Roman Iberian Peninsula; Gadeira; Gadir; Gades.